A fuzzy inference-based trust model estimation system for service selection in cloud computing. (10th May 2019) - Thomas, Roney; Govindaraj, Priya; Natarajan, Jaisankar
Cloud computing assures to be the fundamental changeover in the evolution of the computing world. The cloud computing helps the users to have no Capex, which is making a lot of businesses and individuals to it. Many services are provided by the cloud, for users to meet their application's functional as well as non-functional. Due to the vast number of available services, ambiguous requirements, security and trust measures and efficiency provided by different cloud providers, it is often difficult for the users to select the cloud services. This paper proposes a system that assesses trust of cloud services by providers using a fuzzy-based inference system for selecting the services dynamically.